Beyond Body Mass Index: Health or Illness Is Not About Weight - Portos, Lucía (Revista del Hospital Italiano de Buenos Aires, 2024)
The weight-centered medical approach, based solely on BMI, overlooks biological, psychological, and social aspects, perpetuating stigmas and affecting self-esteem. Comprehensive and respectful evaluations, as recommended by the Ministry of Health guidelines in Argentina, are required to prevent discrimination and promote inclusive and appropriate care.
Keywords: body mass index; pesocentrist; controversy